2022
DOI: 10.16899/jcm.1033380
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significant of tumor budding, tumor stroma ratio and tumor-infiltrating lymphocytes in gallbladder adenocarcinoma

Abstract: Tumor microenvironment plays an important role in onset and progression of the cancer. Tumor budding (TB), tumor stroma and tumorinfiltrating lymphocytes are component of the tumor microenvironment. It was aim to determine the relationship of TB, tumor stroma ratio (TSR) and tumor-infiltrating lymphocytes (TILs) with clinicopathological prognostic parameters in gallbladder adenocarcinoma.Material and Method: Thirty cholecystectomy cases that were diagnosed as adenocarcinoma between 2010 and 2020, that did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The study of tumor budding and TILs in GBC is particularly important due to the limited literature available on this subject [ 6 9 ]. As of now, there has been only one study in the literature that evaluated the association of both TILs and tumor budding in GBC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of tumor budding and TILs in GBC is particularly important due to the limited literature available on this subject [ 6 9 ]. As of now, there has been only one study in the literature that evaluated the association of both TILs and tumor budding in GBC.…”
Section: Discussionmentioning
confidence: 99%
“…As of now, there has been only one study in the literature that evaluated the association of both TILs and tumor budding in GBC. Secinti et al [ 6 ] conducted this study, assessing the prognostic role of these biomarkers. Their study revealed significant associations between high tumor budding and adverse clinicopathological features, including higher tumor grade, advanced tumor stage, nodal and distant metastasis, as well as lymphovascular invasion.…”
Section: Discussionmentioning
confidence: 99%